Acupressure to Reduce Treatment-Related Symptoms for Children With Cancer and Recipients of Hematopoietic Stem Cell Transplant: Protocol for a Randomized Controlled Trial - E Anne Lown DrPH; Anu Banerjee MD; Eric Vittinghoff PhD; Christopher C Dvorak MD; Wendy Hartogensis PhD; Alexis Melton MD, PhD; Christina Mangurian MD; Hiroe Hu BA; Deborah Shear BA; Robyn Adcock LAc; Michael Morgan LAc; Carla Golden MD; et al. (SAGE Publishing, 2019)
Background We describe the study design and protocol of a pragmatic randomized controlled trial (RCT) Acupressure for Children in Treatment for a Childhood Cancer (ACT-CC). Objective To describe the feasibility and effectiveness of an acupressure intervention to decrease treatment-related symptoms in children in treatment for cancer or recipients of a chemotherapy-based hematopoietic stem cell transplant (HSCT). Design Two-armed RCTs with enrollment of 5 to 30 study days. Setting Two pediatric teaching hospitals. Patients Eighty-five children receiving cancer treatment or a chemotherapy-based HSCT each with 1 parent or caregiver. Intervention Patients are randomized 1:1 to receive either usual care plus daily professional acupressure and caregiver delivered acupressure versus usual care alone for symptom management. Participants receive up to 20 professional treatments. Main Outcome A composite nausea/vomiting measure for the child. Secondary Outcomes Child's nausea, vomiting, pain, fatigue, depression, anxiety, and positive affect. Parent Outcomes Depression, anxiety, posttraumatic stress symptoms, caregiver self-efficacy, and positive affect. Feasibility of delivering the semistandardized intervention will be described. Linear mixed models will be used to compare outcomes between arms in children and parents, allowing for variability in diagnosis, treatment, and age. Discussion Trial results could help childhood cancer and HSCT treatment centers decide about the regular inclusion of trained acupressure providers to support symptom management.